The Poetical Works of Edward Taylor - Johnson, Thomas Herbert (Princeton, NJ : Princeton University Press, 2015)
From a 250 year-old manuscript come these selections from the work of America's first important poet, Edward Taylor of Massachusetts. He was regarded by Mark Van Doren as the writer of "the most interesting American verse before the 19th century."Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Foreword to The Paperback Edition -- Foreword -- Edward Taylor -- His Poetry -- Gods Determinations -- Five Poems -- Sacramental Meditations -- Glossary -- Notes to This Edition -- Taylor's Library -- A Description of The Manuscript "Poetical Works" -- Bibliography
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Poetry; POETRY / General